2008
DOI: 10.1007/s10585-008-9183-1
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to mesenchymal transition (EMT) in human prostate cancer: lessons learned from ARCaP model

Abstract: Androgen refractory cancer of the prostate (ARCaP) cells contain androgen receptor (AR) and synthesize and secrete prostate specific antigen (PSA). We isolated epithelia-like ARCaP(E) from parental ARCaP cells and induced them to undergo epithelial-mesenchymal transition (EMT) by exposing these cells to soluble factors including TGFbeta1 plus EGF, IGF-1, beta2-microglobulin (beta2-m), or a bone microenvironment. The molecular and behavioral characteristics of the resultant ARCaP(M) were characterized extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(163 citation statements)
references
References 40 publications
5
157
1
Order By: Relevance
“…Upon exposure to certain soluble factors or host bone microenvironment, low-invasive and epithelial-like ARCaP E cells undergo EMT and acquire invasive properties (26,27). Western blot analysis showed that both EGFR and neu (HER2/ ErbB2) were highly expressed and phosphorylated in ARCaP E cells and their highly metastatic, mesenchymal-like counterparts ARCaP M cells (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Upon exposure to certain soluble factors or host bone microenvironment, low-invasive and epithelial-like ARCaP E cells undergo EMT and acquire invasive properties (26,27). Western blot analysis showed that both EGFR and neu (HER2/ ErbB2) were highly expressed and phosphorylated in ARCaP E cells and their highly metastatic, mesenchymal-like counterparts ARCaP M cells (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…35 Therefore, we defined by Western Blot analysis the expression profiles of the proteins involved in EMT in normal and hypoxic conditions and their variations following ANXA1 downregulation. Our results showed a significant reversion of EMT process upon ANXA1 knock down in normoxia and hypoxia exposed PCa cells suggested by noteworthy E-cadherin enhancement and vimentin decrease (Fig.…”
Section: Anxa1 Expression Strictly Correlates With Pca Cell Mesenchymmentioning
confidence: 99%
“…Furthermore, we found that recombinant 2-m protein could phosphorylate the Bcl-xL/Bcl-2-associated death-promoting protein, Bad, at Ser136 and Ser112 via activated PI3K/Akt and ERK signaling pathways in renal carcinoma SN12C cells [33]. Using a robust human prostate cancer EMT progression model, Zhau et al [63] from our group also showed that 2-m stably transfected ARCaP E prostate cancer cells had consistently activated STAT3, Snail, LIV-1, and overexpressed LIV-1 and receptor activator of nuclear factor kappa B ligand (RANKL)…”
Section: Roles Of 2-m In Signaling Pathways In Cancer Cellsmentioning
confidence: 96%
“…Previous studies have supported the association of increased EMT with the ability of cancer cells to migrate, invade, and metastasize to the skeleton. 2-m also regulates cancer bone metastasis and confers cancer lethality through EMT by downregulation of E-cadherin and upregulation of N-cadherin, vimentin, and RANKL in solid tumors [34,63].…”
Section: Roles Of 2-m In Interaction Between Cancer Cells and Bone MImentioning
confidence: 99%